Do Cupins Have a Function Beyond Being Seed Storage Proteins? - Gábrišová, Daša; Klubicová, Katarína; Danchenko, Maksym; Gömöry, Dušan; Berezhna, Valentyna V.; Skultety, Ludovit; Miernyk, Ján A.; Rashydov, Namik; Hajduch, Martin (Frontiers in Plant Science, 2016)
Plants continue to flourish around the site of the Chernobyl Nuclear Power Plant disaster. The ability of plants to transcend the radio-contaminated environment was not anticipated and is not well understood. The aim of this study was to evaluate the proteome of flax (Linum usitatissimum L.) during seed filling by plants grown for a third generation near Chernobyl. For this purpose, seeds were harvested at 2, 4, and 6 weeks after flowering and at maturity, from plants grown in either non-radioactive or radio-contaminated experimental fields. Total proteins were extracted and the two-dimensional gel electrophoresis (2-DE) patterns analyzed. This approach established paired abundance profiles for 130 2-DE spots, e.g., profiles for the same spot across seed filling in non-radioactive and radio-contaminated experimental fields. Based on Analysis of Variance (ANOVA) followed by sequential Bonferroni correction, eight of the paired abundance profiles were discordant. Results from tandem mass spectrometry show that four 2-DE spots are discordant because they contain fragments of the cupin superfamily-proteins. Most of the fragments were derived from the N-terminal half of native cupins. Revisiting previously published data, it was found that cupin-fragments were also involved with discordance in paired abundance profiles of second generation flax seeds. Based on these observations we present an updated working model for the growth and reproductive success of flax in a radio-contaminated Chernobyl environment. This model suggests that the increased abundance of cupin fragments or isoforms and monomers contributes to the successful growth and reproduction of flax in a radio-contaminated environment.